2018
DOI: 10.3892/etm.2018.6073
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of Schisandra polysaccharides in cyclophosphamide‑induced immunocompromised mice

Abstract: As a strategy to prevent the well-known immunosuppressant effects of cyclophosphamide (Cyp), the immunomodulatory effects of the polysaccharide extract of the fruit of Schisandra chinensis (Turcz.) Baill. were investigated in the present study. The crude Schisandra polysaccharide (SCP) was obtained by water extraction and alcohol precipitation methods. The total carbohydrate, uronic acid and protein contents were determined using the phenol-sulfuric acid, m-hydroxydiphenyl and Bradford method, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…A decrease in the number of phagocytes causes disorders of certain immune factors, leading to a decrease in immune function. The administration of Schisandra polysaccharides significantly inhibits the decrease in phagocytes in mice immune compromised with cyclophosphamide (Yu et al, 2018). The results of the present study indicated that crude polysaccharide of C. versicolor significantly inhibits the decrease in the number of phagocytes in mice immune dysfunction induced M. forfoitum.…”
Section: Effect Of Crude Polysaccharides Of C Versicolor On the Numbsupporting
confidence: 54%
“…A decrease in the number of phagocytes causes disorders of certain immune factors, leading to a decrease in immune function. The administration of Schisandra polysaccharides significantly inhibits the decrease in phagocytes in mice immune compromised with cyclophosphamide (Yu et al, 2018). The results of the present study indicated that crude polysaccharide of C. versicolor significantly inhibits the decrease in the number of phagocytes in mice immune dysfunction induced M. forfoitum.…”
Section: Effect Of Crude Polysaccharides Of C Versicolor On the Numbsupporting
confidence: 54%
“…In addition, mice in Group 1 (normal control group) were received and injected an equivalent volume of sterile saline with same producer for comparison. On day-19, the animals were sacrificed by CO 2 asphyxiation, and the thymus, spleen and serum were harvested for future determinations [11]. All the experimental protocols were in accordance with the National Institutes of Health guidelines for the Care of Use of Laboratory Animals, and approved by the Animal Research Ethics Committee (reference No: UMARE-014-2017), University of Macau, Macao SAR, China.…”
Section: Methodsmentioning
confidence: 99%
“…51,52 The apoptosis of immune cells is closely related to the regulation of the immune system, and is an important index to evaluate the changes of immune function. 53 As important regulators of apoptosis, the expressions of both anti-apoptotic proteins represented by Bcl2 and pro-apoptotic proteins represented by Bax and Caspase-3 determine the trend of apoptosis. 54,55 Interestingly, apoptosis is also related to Nrf2.…”
Section: Discussionmentioning
confidence: 99%